Mooseer (Allium hirtifolium) boosts growth, general health status, and resistance of rainbow trout (Oncorhynchus mykiss) against Streptococcus iniae infection. Issue 120 (January 2022) - Rashidian, Ghasem; Mahboub, Heba H.; Fahim, Azin; Hefny, Ahmed A.; Prokić, Marko D.; Rainis, Simona; Boldaji, Javad Tahmasebi; Faggio, Caterina
Abstract: In large-scale aquaculture, the fast growth rate of fish is positively influenced by feed additives such as medicinal plants. This is however; infectious disease may reduce fish growth and cause devastating economic loss. The present study investigated in vitro antibacterial efficacy of Mooseer ( Allium hirtifolium ) extract against Streptococcus iniae and its in vivo effects on growth, biochemical parameters, innate immunity of rainbow trout ( Oncorhynchus mykiss ). Therefore, six experimental diets were designed to include different levels of Mooseer from zero (as control), 5, 10, 15, 20, and 25 g per kg diet respectively referred to as M1 to M5. Results from the antibacterial evaluation showed that Mooseer extract inhibits S. iniae growth with MIC and MBC values of 128 and 256 μg ml −1 . Appreciable results were obtained in the groups supplemented with Mooseer. Mooseer enhanced growth performance, and modulated serum biochemical and immunological parameters (total protein, albumin, triglyceride, glucose, cortisol, cholesterol, lysozyme, Ig, ACH50, ALP, and protease activity), and liver enzymes (ALT, AST and ALP). The greatest effects were found for higher doses of Mooseer supplementation (M4 and M5). Meanwhile, results from the survival rate of fish challenged with S. iniae showed higher survival in M2 and M4 treatments. The present findings suggest the beneficial use of Mooseer in rainbow trout diet, with 20 g kg −1 inclusion as the recommended dose. Highlights: Mooseer extract inhibits Streptococcus iniae growth in vitro. Supplementation of diet with Mooseer boost growth rate of rainbow trout. Mooseer enhances immunological responses and disease resistance in rainbow trout.